2015
DOI: 10.1016/j.bmcl.2014.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering potential ‘herbal probiotics’ in Juzen-taiho-to through the study of associated bacterial populations

Abstract: Juzen-taiho-to (JTT) is an immune-boosting formulation of ten medicinal herbs. It is used clinically in East Asia to boost the human immune functions. The active factors in JTT have not been clarified. But, existing evidence suggests that lipopolysaccharide (LPS)-like factors contribute to the activity. To examine this possibility, JTT was subjected to a series of analyses, including high resolution mass spectrometry, which suggested the presence of structural variants of LPS. This finding opened a possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
(37 reference statements)
2
19
0
Order By: Relevance
“…The mean in vitro activity exhibited by the E. purpurea extracts can be accounted for by the activities and prevalence of Proteobacteria alone, substantiating that components from Proteobacteria are responsible for the in vitro macrophage activation exhibited by extracts of E. purpurea aerial material. A similar finding was recently reported by Montenegro et al [8] who found Proteobacteria of the genus Rahnella was the most abundant taxa in the root material from Angelica sinensis , and its prevalence was correlated with in vitro macrophage activation by extracts of this plant.…”
Section: Discussionsupporting
confidence: 90%
“…The mean in vitro activity exhibited by the E. purpurea extracts can be accounted for by the activities and prevalence of Proteobacteria alone, substantiating that components from Proteobacteria are responsible for the in vitro macrophage activation exhibited by extracts of E. purpurea aerial material. A similar finding was recently reported by Montenegro et al [8] who found Proteobacteria of the genus Rahnella was the most abundant taxa in the root material from Angelica sinensis , and its prevalence was correlated with in vitro macrophage activation by extracts of this plant.…”
Section: Discussionsupporting
confidence: 90%
“…27,28 In fact, plant-colonizing microorganisms such as Rahnella species have been linked to the immunostimulatory effects of Angelicae Radix, a central ingredient of TSS. 27,28 In fact, plant-colonizing microorganisms such as Rahnella species have been linked to the immunostimulatory effects of Angelicae Radix, a central ingredient of TSS.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies propose the new concept that glycolipid factors derived from bacteria colonizing medicinal plants contribute to the immune-boosting activities. 27,28 In fact, plant-colonizing microorganisms such as Rahnella species have been linked to the immunostimulatory effects of Angelicae Radix, a central ingredient of TSS. 28 In this context, the molecular interaction of bacteria-derived glycolipid components in TSS with iNKT cells could be a compelling target for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that the immunostimulatory factors in Echinacea and JTT were lipopolysaccharides (LPSs) of plant‐associated Gram‐negative bacteria (Haron et al, ; Kalpana et al, ; Montenegro et al, ; Pugh, Jackson, & Pasco, ; Pugh et al, ; Todd et al, ). These findings opened a possibility that the immunostimulatory activity of other medicinal plants might also arise from LPSs.…”
Section: Introductionmentioning
confidence: 99%